The Islamic enlightenment the struggle between faith and reason : 1798 to modern times - De Bellaigue, Christopher 1971- (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2017)
A revelatory and game-changing narrative that rewrites everything we thought we knew about the modern history of the Islamic world. With majestic prose, Christopher de Bellaigue presents an absorbing account of the political and social reformations that transformed the lands of Islam in the nineteenth and early twentieth centuries. Flying in the face of everything we thought we knew, The Islamic Enlightenment becomes an astonishing and revelatory history that offers a game-changing assessment of the Middle East since the Napoleonic Wars. Beginning his account in 1798, de Bellaigue demonstrates how Middle Eastern heartlands have long welcomed modern ideals and practices, including the adoption of modern medicine, the emergence of women from seclusion, and the development of democracy. With trenchant political and historical insight, de Bellaigue further shows how the violence of an infinitesimally small minority is in fact the tragic blowback from these modernizing processes. What makes The Islamic Enlightenment particularly germane is that non-Muslim pundits in the post-9/11 era have repeatedly called for Islam to subject itself to the transformations that the West has already achieved since the Enlightenment--the absurd implication being that if Muslims do not stop reading or following the tenets of the Qur'an and other holy books, they will never emerge from a benighted state of backwardness. The Islamic Enlightenment, with its revolutionary argument, completely refutes this view and, in the process, reveals the folly of Westerners demanding modernity from those whose lives are already drenched in it.